An Alternative DAO-Based Financing Strategy for Microenterprises: International Insights from Japan - Oba, Yoshiyuki (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation examines the potential of Decentralized Autonomous Organizations (DAOs) as an alternative financing model for microenterprises, with a specific focus on pioneering cases of Japanese microenterprises. Microenterprises worldwide face persistent financing constraints, often relying solely on bank loans under asymmetric information and limited collateral. Against this backdrop, blockchain-enabled DAOs offer novel possibilities for transparency, collective governance, and innovative capital formation mechanisms that may complement conventional MSME finance. The study employs a qualitative design, integrating a systematic literature review with nine case studies of Japanese DAO LLCs. Semi-structured interviews with these DAO founders, combined with secondary sources such as governance documents and community publications, provided the empirical foundation. Findings reveal recurring success factors—including community engagement, transparent governance, and access to decentralized finance (DeFi) platforms—while also highlighting major challenges in treasury management, regulatory ambiguity, and sustainable business modeling. Cross-case analysis demonstrates that DAOs can mitigate trust and resource mobilization issues but remain constrained by legal uncertainty and operational immaturity. Beyond national relevance, the Japanese DAO experience holds international significance. Japan represents one of the jurisdictions to integrate blockchain-based DAOs into existing company law, providing a unique laboratory for global policy and practice. Lessons from Japanese MSMEs are particularly relevant for emerging economies, where MSMEs often face severe financing gaps. DAOs, if properly regulated, may serve as complementary mechanisms to enhance financial inclusion and resilience in local MSME ecosystems. The dissertation contributes theoretically to the field of MSME finance by extending concepts of relationship banking and credit assessment into decentralized governance environments. It shows how DAO mechanisms can complement existing theories of MSME finance, alleviating information asymmetry as the key issue and offering a hybrid financing model that integrates community-based trust with blockchain-enabled transparency. In conclusion, DAOs present a promising yet still nascent pathway for supporting microenterprises. Practical implications include the need for regulatory clarity, institutional experimentation, and closer integration with community banking models. Future research should pursue longitudinal studies tracking the Japanese DAO LLCs with quantitative analysis, as well as comparative case studies across different jurisdictions. Keywords: Alternative Financing Strategy; Blockchain; Decentralized Autonomous Organization (DAO); Emerging Economies; Information Asymmetry; Japan; Microenterprises, MSME Finance